Pancreatic solid cystic desmoid tumor: Case report and literature review - Xu, Bin (Baishideng Publishing Group Co., Limited, 2013)
Desmoid tumors (DTs) are nonmetastatic, locally aggressive neoplasms with a high rate of postoperative recurrence. Pancreatic DTs are especially rare; only a few cases have been reported to date. This paper describes a case of a sporadic cystic DT of the pancreas managed successfully with central pancreatectomy, with no signs of recurrence 40 mo after surgery. According to the literature, this is the first reported case in China of a pancreatic DT presenting as a solid cystic lesion, as well as the first pancreatic DT managed with central pancreatectomy and pancreaticogastrostomy. We report the case for its rarity and emphasize disease management by concerted application of clinical, pathological, radiological and immunohistochemical analyses.